First description of agonistic behaviour in Chondrostoma polylepis (Pisces: Cyprinidae) with notes on the behaviour of other Chondrostoma species - Robalo, Joana Isabel (2012)
In this paper we describe for the first time the occurrence of agonistic behaviour in Chondrostoma polylepis (Pisces: Cyprinidae) in captivity. In this species agonistic behaviour was present in adults of both sexes and juveniles, during spring and summer, well after the end of the breeding season. Qualitative observations revealed the presence of a similar pattern of agonistic behaviour in Chondrostoma duriensis. Despite intense observation effort, no signs of agonistic behaviour were detected in three other Chondrostoma species of the same geographical area, C. macrolepidotus, C. lemmingii and C. lusitanicum. It is hypothesized that agonistic behaviour in C. polylepis and C. duriensis may be functionally linked to their feeding ecology.